Radiation-induced lymphopenia and the survival of women with cervical cancer: a meta-analysis - Hongming Cao; Haiyan Yan; Shoumin Bai; Baihui Gu (Journal of Obstetrics and Gynaecology, 2023)
The current systematic analysis and meta-analysis was aimed to evaluate the association between radiation-induced lymphopenia (RIL) and survival of women with cervical cancer (CC). PubMed, Embase, Web of Science, and Cochrane Library were searched for relevant cohort studies comparing survival between women with CC who developed versus not developed RIL after radiotherapy. We pooled the results using a random-effects model that incorporates heterogeneity. In the meta-analysis, 952 women with CC were included from eight cohort studies. Overall, 378 (39.7%) of them had RIL after radiotherapy. During a median follow-up duration of 41.8 months, pooled results showed that RIL was independently associated with poor overall survival (hazard ratio [HR]: 2.67, 95% confidence interval [CI]: 1.81 to 3.94, p < 0.001; I2 = 20%) and progression-free survival (HR: 2.17, 95% CI: 1.58 to 2.98, p < 0.001; I2 = 0%). Predefined subgroup analyses showed similar results in patients with grade 3-4 and grade 4 RIL, in patients with RIL diagnosed during or after the radiotherapy, and in studies with quality score of seven or eight points (p values for subgroup effect all < 0.05). In conclusion, women with RIL were associated with poor survival after radiotherapy for CC.